Strengthening Education on National Defense and Security to Fulfill the Needs of Early and Distant Homeland Safeguarding - CAO, Ngoc Bau; TRAN, Mong Nghi (Journal of Ecohumanism, 2024)
This article provides an analysis and evaluation of the current situation of national defense and security education in Vietnam, with a particular focus on the crucial role that education plays in the process of constructing and safeguarding the nation. The research highlights the accomplishments that have been made in the areas of leadership, direction, program development, teacher training, and infrastructure for the education of national defense and security forces. The article, which is based on this evaluation, suggests ideas to innovate and enhance the quality and efficacy of education regarding national defense and security in order to meet the criteria of early and remote homeland protection.